Integration of paper spray ionization high‐field asymmetric waveform ion mobility spectrometry for forensic applications. (5th March 2018) - Tsai, Chia‐Wei; Tipple, Christopher A.; Yost, Richard A.
Abstract : Rationale: Paper spray ionization (PSI) is an attractive ambient ionization source for mass spectrometry (MS) since it allows the combination of surface sampling and ionization. The minimal sample preparation inherent in this approach greatly reduces the time needed for analysis. However, the ions generated from interfering compounds in the sample and the paper substrate may interfere with the analyte ions. Therefore, the integration of PSI with high‐field asymmetric ion mobility spectrometry (FAIMS) is of significant interest since it should reduce the background ions entering the mass analyzer without complicating the analysis or increasing analysis time. Here we demonstrate the integration of PSI with FAIMS/MS and its potential for analysis of samples of forensic interest. Methods: In this work, the parameters that can influence the integration, including sampling and ionization by paper spray, the FAIMS separation of analytes from each other and background interferences, and the length of time that a usable signal can be observed for explosives on paper, were evaluated with the integrated system. Results: In the negative ion analysis of 2, 4, 6‐trinitrotoluene (TNT), pentaerythritol tetranitrate (PETN), octahydro‐1, 3, 5, 7‐tetranitro‐1, 3, 5, 7‐tetrazocine (HMX), and 1, 3, 5‐trinitroperhydro‐1, 3, 5‐triazine (RDX), amounts as low as 1 ng on paper were readily observed. The successful positive ion separation of a set of illicit drugs including heroin, methamphetamine, and cocaine was also achieved. In addition, the positive ion analysis of the chemical warfare agent simulants dimethyl methylphosphonate (DMMP) and diisopropyl methylphosphonate (DIMP) was evaluated. Conclusions: The integration of PSI‐FAIMS/MS was demonstrated for the analyses of explosives in negative ion mode and for illicit drugs and CW simulants in positive mode. Paper background ions that could interfere with these analyses were separated by FAIMS. The compensation voltage of an ion obtained by FAIMS provided an additional identification parameter to be combined with the mass spectrum for each analyte.